A New Tracking Loop Scheme for High Dynamics Real-Time GNSS Receivers with Hardware Correlators - Roncagliolo, Pedro Agustín (2016)
In this paper the implementation of one-delay carrier tracking loops in GNSS receivers that utilized hardware correlators is proposed. The previously adopted two-delay solutions were justified in the necessity of providing a phase reference to the correlator before the beginning of the correlation interval. However, this constraint can be relaxed by utilizing other phase reference and compensating the resulting correlation value accordingly after its computation. The proposed one-delay loop implementation is particularly useful for high dynamics conditions and therefore the UFA-PLL structure associated with an optimal digital loop filter was adopted for the analysis presented in this work. The optimum digital loop filter structures, previously derived for the case of two-delay carrier tracking loops, are updated under the one-delay condition. The obtained results are quite similar, with the novelty that the extra pole present in the former solution is not present any more. Two particular cases are analyzed by simulation to determine the pull-out performance and the associated tracking thresholds. First, a loop with correlation time of T = 10ms is shown to be able to track acceleration steps of 20g with similar performance than the previously obtained using two-delay implementations with T = 5ms and the same 75.6Hz bandwidth. In this case, doubling the correlation time imply a great reduction in the computational burden. Secondly, the same pull-out performance is shown in two T = 10ms loops, one with two delays and 37.8Hz bandwidth and the other with one delay and 19.8Hz bandwidth. In this case, half bandwidth imply half variance of the estimated phase, which is equivalent to an improvement of 3dB in the signal to noise ratio.